The secret of the lost gold - Elliott, Rebecca (2025)
In the dark woods a griffin guards a secret cave and the old king's gold, but now Queen Juniper needs the gold to help restore the forest after a bad storm, so Bo and the unicorns seek out the griffin hoping to explain their need.
Keywords: Unicorns -- Juvenile fiction; Griffins -- Juvenile fiction; Magic -- Juvenile fiction; Severe storms -- Juvenile fiction; Diaries -- Juvenile fiction; Unicorns -- Fiction; Griffins -- Fiction; Magic -- Fiction; Natural disasters -- Fiction; Diaries -- Fiction